CHLORIDE STRESS CORROSION CRACKING FOR 304L AUSTENITIC STAINLESS STEEL - TAJUL ARIFFIN, MOHD ARIF (IRC, 2017)
Stress corrosion cracking (SCC) is a failure phenomenon which occurs under conditions of constant applied stress for particular combinations of alloy/ material and environment. Up to date, Chloride Stress Corrosion Cracking (CLSCC) is one of the most widely recognized corrosion problems why austenitic stainless steel pipework and vessels deteriorate in the chemical processing and petrochemical industries. The aim of this project is to study the impact of sodium chloride concentration and impact of applied strain towards the SCC initiation of 304L stainless steel specimen. The test specimens were prepared and machined into C-ring geometry accordingly to ASTM G38-01 standard. Then they were stressed by tightening with bolt and nut into 0.4% (low material yield stress) and 1.2% strain (high material yield stress). All C-ring specimens were submerged in a beaker at temperatures 50°C with different Sodium Chloride (NaCl) solution concentrations at 0.1 wt. %, 1.0 wt. % and 3.0 wt. % which corresponds to low, medium and high concentration respectively. Optical examination on the C-ring specimen’s surface after 60 days showed that stress corrosion cracking did not occur on any specimens. But the formation of Pitting Corrosion occurs at different severity on different specimens. C-Ring specimen with high strain immersed in high NaCl solution showed the highest Pitting Corrosion severity than other specimens.